Pendampingan Pemanfaatan Aplikasi Corn Disease Detector (Coditor) untuk Identifikasi Penyakit Tanaman Jagung Bagi Kelompok Tani Dewa Buluran - Khaira, Ulfa; Adriadi, Ade; Arsa, Daniel; Noverina, Yolla; Nugraha, Anggit Prima (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
The Dewa Buluran Farmers Group often faces difficulties in accurately and timely identifying corn plant diseases. This is due to a lack of knowledge and information about corn plant diseases and the appropriate control methods. Farmers heavily rely on chemical fertilizers and pesticides for pest control, and sometimes the application of these chemicals is not in the correct dosage, resulting in poor corn plant growth.Therefore, it is necessary to conduct a mentoring activity to utilize the Coditor (Corn Disease Detector) application for identifying corn plant diseases and implementing appropriate and effective corn plant disease control using biological agents for the Dewa Buluran Farmers Group. This activity aims to improve the knowledge and ability of the Dewa Buluran Farmers Group in identifying corn plant diseases and being able to utilize biological agents in pest control. This activity was attended by extension workers, plant pest and disease control officers, and 25 members of the Dewa Buluran Farmers Group. The activity was held on September 26, 2024, at the Dewa Buluran Farmers Group's house. The community service activities were carried out in several stages, namely a survey of the problems faced by partners, training and mentoring, and evaluation. The results of this activity show an increase in farmers' understanding of identifying types of pests and diseases of corn plants, and farmers are able to apply pest management technology by utilizing biological agents.